Perbandingan Perlakuan Hukum terhadap Terdakwa Tindak Pidana Perdagangan Orang oleh Kejaksaan Negeri Sikka: Studi Kasus Yuvinus Solo dan Karolus Kartinus Kotin di Kabupaten Sikka (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the factors causing the differences in legal treatment and their implications on the principles of equality before the law, legal certainty, and the principle of legality. The method used is empirical legal research with a juridical-sociological approach. This study involves case studies, interviews with law enforcement officers and victim advocates, as well as an analysis of regulations and court decisions. The results indicate that the differences in legal treatment are caused by the application of subjective detention requirements in the Criminal Procedure Code (KUHAP), law enforcement discretion, differing legal interpretations between prosecutors and judges, the quality of legal assistance for defendants, and social pressures and societal dynamics. The impact of these differences is the failure to achieve substantive justice, weakening legal certainty, and declining public trust in the criminal justice system. This research has significant academic urgency as it contributes to the development of the enforcement of laws regarding Human Trafficking (TPPO), emphasizing the need for consistency, transparency, and the protection of victims' rights in the application of criminal law.